PROPORTIONAL-INTEGRAL-DERIVATIVE (PID) CONTROLLER TUNING FOR AN INVERTED PENDULUM USING PARTICLE SWARM OPTIMISATION (PSO) ALGORITHM - Joseph, S. B.; Dada, E. G. (FUDMA Journal of Sciences, 2023)
Linear control systems can be easily tuned using conventional tuning techniques such as the Ziegler- Nichols and Cohen-Coon tuning formulae. Empirical studies have found that these conventional tuning methods result in an unsatisfactory control performance when they are used for industrial processes. It is for this reason that control practitioners often prefer to tune most nonlinear systems using trial and error tuning, or intuitive tuning. A need therefore exists for the development of a suitable automatic tuning technique that is applicable for a wide range of control processes that do not respond satisfactorily to conventional tuning. The balancing of an inverted pendulum by moving a cart along a horizontal track is a classic problem in the area of control. The encouraging results obtained from the simulation of the PID Controller parameters-tuning using the PSO when compared with the performance of PID and Ziegler-Nichols (Z-N) makes PSO-PID a good addition to solving PID Controller tuning problems using metaheuristic techniques as will reduce the time and cost of tuning these parameters and improve the overall system performance.
Keywords: Inverted Pendulum, PID Controller, Particle Swarm Optimization Algorithm, Ziegler- Nichols method, tuning